Sli15 Associates with the Ipl1 Protein Kinase to Promote Proper Chromosome Segregation in Saccharomyces cerevisiae - Kim, Jae-hyun (The Rockefeller University Press, 1999)

(untitled)
The conserved Ipl1 protein kinase is essential for proper chromosome segregation and thus cell viability in the budding yeast Saccharomyces cerevisiae. Its human homologue has been implicated in the tumorigenesis of diverse forms of cancer. We show here that sister chromatids that have separated from each other are not properly segregated to opposite poles of ipl1-2 cells. Failures in chromosome segregation are often associated with abnormal distribution of the spindle pole–associated Nuf2-GFP protein, thus suggesting a link between potential spindle pole defects and chromosome missegregation in ipl1 mutant cells. A small fraction of ipl1-2 cells also appears to be defective in nuclear migration or bipolar spindle formation. Ipl1 associates, probably directly, with the novel and essential Sli15 protein in vivo, and both proteins are localized to the mitotic spindle. Conditional sli15 mutant cells have cytological phenotypes very similar to those of ipl1 cells, and the ipl1-2 mutation exhibits synthetic lethal genetic interaction with sli15 mutations. sli15 mutant phenotype, like ipl1 mutant phenotype, is partially suppressed by perturbations that reduce protein phosphatase 1 function. These genetic and biochemical studies indicate that Sli15 associates with Ipl1 to promote its function in chromosome segregation.